Assessment on the Prevention and Control System for Corona Virus 2019 (COVID-19) in Phaholpolphayuhasena Hospital, Kanchanaburi Province - เหล่าลือเกียรติ สมเจตน์; เวียงเจริญ รักษ์พงศ์; พิพัฒน์นรเศรษฐ ศุภฌา; อนันตริยกุล ชนากานต์ (Journal of Health Science of Thailand, 2023)
The purposes of study was to assess the current management for the prevention and control of corona virus disease 2019 (COVID-19) in Phaholpolphayuhasena Hospital, Thailand; and to develop management prevention and control of COVID-19 in Phaholpolphayuhasena Hospital, Kanchanaburi Province. This research was conducted using mixed method comprising of a quantitative research and a qualitative research. The sample groups were the heads of Phaholpolphayuhasena Hospital Group consisted of doctors, nurses using questionnaires and in-depth interviews, 36 people. The results showed that among the 38 issues raised, the highest one was the formation of emergency operation center (EOC) which had monthly meeting. From the interview form, it was found that management for the prevention and control of COVID-19) of Phaholpolphayuhasena Hospital involved the policy translation on the measures recommended by the EOC to implementers in the hospital. In addition, there were close monitoring and following-up of the disease control measures. Changes or adjustment in the measures would be followed by the consultation process to ensure proper understanding. The guidelines development, screenings and staff adjustment were continuously conducted in accordance with the situation. Most importanly, the EOC and the regularmeeting were well functioned to ensure the effectiveness of the COVID-19 control.